Analysis of Problems and Solutions in Social Studies Learning at Elementary Schools - A. Gafar Hidayat; Tati Haryati (JURNAL PENDIDIKAN IPS, 2023)
The purpose of writing this article is; 1) describe the problems of social studies learning in elementary schools; 2) identify solutions to social studies learning problems in elementary schools. The method used in writing this article is a literature review or literature study, which uses theories and reference approaches that are relevant to the problem topic of writing this article. The steps for analyzing literature studies are; 1) describe the comparison and relevance of references that will be used to examine the topic problem; 2) matrix mapping according to data and reference needs; 3) establish concepts that are contextual to the topic problem, so that they can be linked to each other. Based on the results of the literature study conducted, it is clear that; 1) Social studies learning problems in elementary schools include; the material presented is less contextual to real life, development of problem solving skills is not carried out; textbook-based learning approach; and students' disruptive behavior often occurs in learning; 2) Solutions for handling social studies learning problems include; minimizing abstract material and focusing on issues that develop in everyday life to make it more contextual, selecting appropriate learning strategies and approaches to create meaningful learning for students, and using technology in learning to increase students' attention and concentration to Avoid disruptive behavior during learning.